Experimental and analytical investigations on sustainable and innovative strengthening systems for masonry arches. (15th February 2019) - Misseri, G.; Rovero, L.; Stipo, G.; Barducci, S.; Alecci, V.; De Stefano, M.
Abstract: The paper deals with the structural behaviour of masonry arches strengthened through fibre reinforced composites with inorganic matrix (Textile Reinforced Mortar, TRM). Two innovative composites are considered: basalt fibre textile coupled with a lime-based matrix and carbon fibre textile associated with a cement-based matrix. Experimental results on bond capacity between composites and bricks and on the structural behaviour of unreinforced and extrados-reinforced, 1:2 scale masonry arches, tested under vertical load are presented. Experimental evidence is compared with outcomes obtained through an analytical model that exploits the stationarity of potential energy of acting forces within the assumption of large displacements. The effect of the reinforcement strip is taken into account retrieving the force-displacement relationship directly from experimental results of bond test. Results show that the analytical model provides a safety estimation of the peak load reached by the arch model during the test. Good agreement is found comparing the load-displacement diagram of the initial phases of the test and the estimations of the numerical model. It is highlighted that the bond force of TRM systems, experimentally determined on a straight substrate, offers capacity levels relevantly under those reached on a convex surface like the extrados of an arch.